Relativistic dynamics of Qqq systems - Suisso, E. F.; de Melo, J. P. [UNESP]; Frederico, T. (My University, 2002)
The bound state of constituent quarks forming a Qqq composite baryon is investigated in a QCD-inspired effective light-front model. The light-front Faddeev equations are derived and solved numerically. The masses of the spin 1/2 low-lying states of the nucleon, Λ0, Λc+ and Λb0, are found and compared to the experimental data. The data are qualitatively described with a flavor independent effective interaction.